Reoperative Thyroid Bed Surgery: An Evaluation of Complications and Outcomes - Sandeep Vijay; Anoop Attakkil; Nikhil Mohan; Raveena Nair; Linu Thomas (Asian Pacific Journal of Cancer Care, 2024)
Introduction: Secondary surgeries for thyroid cancers are conventionally associated with long term morbidities. This study was conducted to assess the efficacy of our Institutional Surgical Protocol while dealing with such cases, through the complications and levels of disease clearance achieved. Methods: It was a retrospective observational study; patients who underwent reoperative thyroid surgery from January 2020 to January 2023 were included. All patients were operated as per the Institutional Policy. Results: 25 patients were included in the study. Secondary surgeries included Central Neck Dissection with Lateral Neck Dissection (40%), Revision thyroidectomy (24%) and Completion thyroidectomy (12%). The pathological diagnoses of the patients were mainly Well differentiated Thyroid cancers like Papillary Carcinoma (72%) and Follicular Carcinoma (12%). Complications following Secondary surgery included Permanent Hypoparathyroidism (4%) and Permanent Vocal cord palsy (4%). Literature shows an incidence of 5-10% and 0-5% respectively. In 60% of patients, there was no uptake in the Postop Iodine scan which displayed complete disease removal. Conclusion: Our Institutional Protocol results in a significant reduction in post op complications as compared to literature. Adequate disease clearance is ascertained by the lack of uptake in the Postop Iodine Scan.